Pinça óptica dupla: análise do comportamento de uma microesfera durante a transição em um poço duplo de potencial - André Gentil Almeida Leite (2016)
In the microscopic world, light can be used as a "mechanical tool". It can do much more than simply illuminate an object, such as, transmitting energy in the form of heat or moment. Therefore, using two optical tweezers it is possible to create a double potential well, which allows you to trap a microsphere and analyze the statistics of its transitions between wells. In this sense, this study veried, experimentally, the dependence of durations with the distance between potentials wells, as well as if these durations are distributions that obey a power law as theoretically envisaged. Thus, from a slave estimator denoted by , referring to a slave equation, the equilibrium of susceptibility of the Lagevin process was analyzed in one dimension x(t) and a potential (t). Then, we build an optical setup with a double optical tweezer to carry out statistical measurements, from a polystyrene microsphere with a diameter of 3 m for three distances between the potential wells (2.87, 3.00 and 3.13 m). The results showed that the behavior of obeys a power law, with exponent , with values growing with longer distances between wells. Comparing the experimental results with the simulation performed, we obtained the same behaviour in both cases.